PROFIL BATIMETRI HABITAT PEMIJAHAN IKAN TERUMBU HASIL INTEGRASI DATA INDERAJA SATELIT DAN AKUSTIK: Studi Kasus Perairan Sekitar Pulau Panggang, Kepulauan Seribu - Syamsul B. Agus; Vincentius P. Siregar; Dietrich G. Bengen; Aryo Hanggono (Fakultas Perikanan dan Ilmu Kelautan, 2012)
Remote sensing technology, both optic and acoustic, serves as major tool for mapping bathymetry synoptically and efficiently. In complex coral cays as Kepulauan Seribu, bathymetric profile may change gradually due to naturally controlled reef accretion/erotion, sand/coral exploitation activities, storms, and mostly several types of fishing techniques (muroami and blast fishing). In this paper, elaboration on bathymetric profiles originated from coupled optic-acoustic dataset will be applied in account for understanding reef fish spawning habitats. A total of 17 reef sites were surveyed in situ to record reef fish with spawning cues (eg: female gravid, male change color, aggregation, etc) in between October 2010-March 2012. A 2008 Quickbird imagery and single beam acoustic data were gridded at 1 m by interpolation using Inverse Distance to Power method resulted in 2-dimension and 3-dimension bathymetric maps thus revealing complex detail of seabed at shallow and deeper depths. Terrain profiles depicting lateral view of bathymetric profile for each reef site were used to describe geomorpological features supporting its role as spawning habitat.